Reckless / 1. - Funke, Cornelia, 1958- (Little, Brown, 2011)
Jacob and Will Reckless have looked out for each other ever since their father disappeared, but when Jacob discovers a magical mirror that transports him to a warring world populated by witches, giants, and ogres, he keeps it to himself until Will follows him one day, with dire consequences.